Transição energética justa frente à expansão das energias renováveis no semiárido nordestino : aspectos jurídicos e socioambientais dos conflitos sob a instalação de parques eólicos - Sampaio, Rárisson Jardiel Santos (2024)
Climate change requires a rapid transformation of the economy towards a low-carbon model. Renewable energies are crucial for the sustainable development of countries and communities. Decentralized systems, for example, have the potential to provide universal access to clean and affordable energy in remote locations or areas lacking adequate infrastructure. Simultaneously, well-managed infrastructure projects and centralized generation can create jobs and stimulate the economy, providing a source of income for small landowners and communities living around these projects. However, in order for these benefits to be realized, an energy and economic policy aligned with the principles of social justice is necessary. This policy should include inclusive processes that consider the participation and effective representation of the interests of the most vulnerable actors. The Brazilian Northeast has the greatest potential for wind energy production in Brazil, with a growing number of wind farms throughout the region. However, the implementation of these activities has involved the appropriation of territory and predatory exploitation of resources, which is contrary to a just transition. The contractual abuse of energy companies for land use and the impacts of the activity have affected rural communities and traditional peoples in the semi-arid region. Contradictorily, the potential for wealth production coexists with socio-environmental conflicts and low economic returns for the families living in the areas where the large projects are located. As a result, civil society organizations and movements have been demanding justice in the energy transition processes, while at the same time seeking to deepen the debate on just transition with authorities and governments at the state and federal levels. This research examines the shape of the energy transition in the semi-arid Northeast of Brazil, focusing on the development of wind farms in the region and the changes that are affecting the social dynamics of the communities affected by these projects. It asks what is the nature of the energy transition process underway in the country, and what elements of justice could guide a just transition in the regional context. The research consists of a qualitative, descriptive and exploratory study, using mainly bibliographic procedures and documentary analysis. The results show that the energy transition in Brazil is predominantly economic, with climate and socio-environmental concerns taking a back seat. A just transition must incorporate principles of equity and improve spheres of governance, making them more inclusive. The exploitation of wind energy has reproduced a neo-extractivist model, generating conflicts and injustices in the territories. The mobilization of society is fundamental to sensitize public actors and political representatives to discuss proposals for a more just energy transition in the semi-arid region.